Arthropods diversity on pea’s field in Kupang Regency East Nusa Tenggara Province - Semiun, Chatarina Gradict; Mamulak, Yulita Iryani (Jurnal Biologi Udayana, 2021)
The success of pea’s cultivation is influenced by the presence of arthropods that act as pollinators, decomposers, parasitoids and bioindicators. This research aimed at determining the diversity of arthropods on pea’s farming lands in Kupang district. This research was a descriptive quantitative research that had been carried out in three locations, namely peanut farming field, long bean farming field, and green bean farming field. Arthropod samples were taken by using pitfall traps, insect nets, and hand sorting. The results showed that arthropod diversity varied in the three pea’s farming lands. First, on peanut farming land, 31 species, 15 families, 9 orders, 2 classes were found, with a total of 115 individuals. Second, on the long bean farming land, 17 species, 11 families, 7 orders, 2 classes were found, with a total of 53 individuals. Last, there were 30 species, 20 families, 9 orders, 3 classes, with a total of 108 individuals found in green bean farming land. The highest diversity index was found in green bean farming land at 3.19, followed by peanut farming land at 2.83, and long bean farming land at 2.43. The highest species richness index value was found in peanut farming land at 6.32, followed by green bean farming land at 6.19, and the lowest in long bean farming land at 4.03. There was no arthropod species that dominated in the three peanut farming lands, the species were classified as evenly distributed. The similarity between Jaccard and peanut habitats showed a value less than 50%, meaning that the similarity level of the arthropod family found in the three pea habitats was low. The low level of similarity could be caused by the application of pesticides, especially in long beans and green beans farming lands. Furthermore, abiotic factors had a significant effect on arthropod diversity.